Comparative Analyses of European Identities in Business – and Every-Day Behaviour: Working and Living Together in Europe - Diehl-Becker, Angela (Facets of Managing in Cross-Cultural Diversity, 2021)
The aim of the project “Comparative Analyses of European Identities in Business and Every- Day Behaviour” (EU-CAB) is to find out whether – regardless of the return to national state positions that has been obvious lately since the peak of the refugee movement in 2015 – a kind of European identity has been built up in the selected European nations. Furthermore, the project seeks to answer whether the perception of behaviour in these countries is similar or varies to a certain degree. The project covers the following EU member states: Finland, France, Hungary, Poland, Portugal, and Germany,1 which were selected according to political and geographical criteria. The project’s staff is multi-disciplinary, including social psychologists and sociologists, engineers, linguists, economists, mathematicians and philosophers.